Current controlled SRM fed by three-phase voltage source converter - Şehi̇rli̇, Erdal; Çakir, Beki̇r; Kuyumcu, Feriha Erfan (IEEE, 2015)
In this paper, simulation of current controlled switched reluctance machine (SRM) which has 6 stator and 4 rotor poles is realized. Furthermore, SRM machine is fed by three phase voltage source converter (VSC) which has six IGBT power switches. The reason of using controlled rectifier is to have higher power factor and also less current harmonics on grid. The current control algorithm of SRM machine is both hysteresis and PI structures. Besides, VSC is controlled by input-output linearization nonlinear control algorithm. Simulations are carried out with Matlab/Simulink. By the simulations, power factor and currents harmonic of grid, current, flux and torque of SRM are presented.
Keywords: 7. Clean energy